Development and characterization of coupled carbon nanotube-titanium dioxide systems - Chan, Yeat Hui. (2010)
In the discovery of photocatalytic properties on Titanium Dioxide (TiO2) by Fujishima and Honda, it is well-known that TiO2 aided in the degradation of pollutants into non-toxic compounds like water and carbon dioxide. However, the efficiency on the photocatalysis by TiO2 is reduced due to the fast recombination rate and the absorption of photons only at Ultra Violet (UV) range. Many researches had been investigated on enhancing the efficiency of the photocatalytic properties by modifying the properties of tio2 and one of the ways is to introduce a supporting material to enhance the photocatalytic properties. In this report, carbon nanotubes (CNTs) acts as ideal sites for absorption of photoinduced charge carriers to increase charge separation time and enhance the photoefficiency. The development and characterization of the coupled carbon nanotubes and titanium dioxide will be discussed in this report. The carbon nanotubes are synthesized by Plasmas Enhanced Chemical Vapor Deposition (PECVD) and functionalized by acids. Functionalization of the CNTs is used to remove the nickel catalyst. In the acid treatment, liquid phase chemical oxidation produces functional groups are produced which form ester-like linkage to enhance the attachment of the CNTs and TiO2 nanoparticles. The effect of the dispersion of titanium dioxide using different pH level will also be discussed. Finally, methylene blue test were done on both pure TiO2 and CNT-TiO2 system to investigate on the degradation of methylene blue in the presence of the CNT-TiO2 photocatalyst. The characterization tools used were: Scanning Electron Microscope (SEM), Energy Dispersive X-rays spectroscopy (EDX), Raman spectroscopy and UV-VIS spectrometer.